Recognizing human emotional states by facial expression analysis for humanoid head AMIR-III - Shafie, Amir Akramin; Iqbal, Aseef; Khan, Md. Raisuddin (2011)
In this paper, we reviewed the existing established methods of facial expression analysis and their limitations in applications. Then we proposed a system for our own robot head AMIR-III. The research used Eigenface method utilizing Principal Component Analysis and Neural Network classifier for emotion recognition from static image frame taken from live video.